2019
DOI: 10.1109/access.2018.2888497
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of Energy Storage Systems, Their Roles, and Impacts on Future Power Systems

Abstract: It is an exciting time for power systems as there are many ground-breaking changes happening simultaneously. There is a global concensus in increasing the share of renewable energy-based generation in the overall mix, transitioning to a more environmental-friendly transportation with electric vehicles as well as liberalizing the electricity markets, much to the distaste of traditional utility companies. All of these changes are against the status quo and introduce new paradigms in the way the power systems ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
201
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(203 citation statements)
references
References 174 publications
(220 reference statements)
0
201
0
2
Order By: Relevance
“…Li-ion chemistry is emerging and consolidated as the most used battery technology. The intrinsic advantages of Li-ion batteries with respect to lead-acid stand as the larger values of the energy and power densities with respect to both unit weight (Wh/kg and W/kg) and unit volume (Wh/L and W/L) [46]. The net results are ESSs that are more compact in size and weight, more efficient for the larger number of charge/discharge cycles possible, and even cost-effective in long-term applications.…”
Section: Energy Storage System Technologies For Micro-gridsmentioning
confidence: 99%
“…Li-ion chemistry is emerging and consolidated as the most used battery technology. The intrinsic advantages of Li-ion batteries with respect to lead-acid stand as the larger values of the energy and power densities with respect to both unit weight (Wh/kg and W/kg) and unit volume (Wh/L and W/L) [46]. The net results are ESSs that are more compact in size and weight, more efficient for the larger number of charge/discharge cycles possible, and even cost-effective in long-term applications.…”
Section: Energy Storage System Technologies For Micro-gridsmentioning
confidence: 99%
“…Stark et al [7] evaluated the available storage concepts and identified the combination of a steam accumulator (SA) with a concrete storage (CS) as the most promising option for flexible biomass CHP plants. Since the 1930s SA are used for the thermal storage of process steam for several industrial sectors, such as the food [8,9] and pharma industry [10,11]. The novelty in this paper does not lie in the SA itself, but in the application of this established technology to support the electricity grid in an energy system that incorporates CS and biomass CHP.…”
Section: Research Approachmentioning
confidence: 99%
“…The submerged vegetation emits methane, which is a GHG with high global warming potential. [10][11][12][13][14][15]…”
Section: Pumped Hydropower Storagementioning
confidence: 99%